Skrining Fitokimia dan Uji Aktivitas Antioksidan Ekstrak Etanol Propolis Lebah Kelulut (Heterotrigona itama): Phytochemical Screening and Antioxidant Activity Test of Kelulut Bee Propolis (Heterotrigona itama) Ethanol Extract - Debby Putri Mutiara Yusuf; Andi Tenri Kawareng; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Kelulut bee propolis (Heterotrigona itama) is one of the products produced by bees in the form of sap as a protective bee hive from predators and is commonly used by the community for treatment. This species also produces propolis more than stinging bees, but its potential has not been explored much. Purpose of this study was to determine the secondary metabolites and antioxidant activity of the ethanolic extract of kelulut bee propolis from Kutai Kartanegara. Propolis was extracted by maceration method using 96% ethanol solvent and evaporated and then carried out phytochemical screening and antioxidant activity test using the DPPH method (2,2-diphenyl-1-picrylhydrazil), ethanol extract of propolis was made in concentrations of 25 ppm, 50 ppm, 100 ppm, 500 ppm, 1000 ppm. The yield value of the propolis ethanol extract was 36% and the phytochemical test showed the presence of flavonoid, alkaloid and phenolic compounds and the IC50 value of the propolis extract was 282.92 ppm. This indicates that kelulut bee propolis containing these secondary metabolites has weak antioxidant activity.